Microbial Diversity of Pinnacle and Conical Microbial Mats in the Perennially Ice-Covered Lake Untersee, East Antarctica - Greco, Carla; Andersen, Dale T.; Hawes, Ian; Bowles, Alexander M. C.; Yallop, Marian L.; Barker, Gary; Jungblut, Anne D. (Frontiers in Microbiology, 2020)
Antarctic perennially ice-covered lakes provide a stable low-disturbance environment where complex microbially mediated structures can grow. Lake Untersee, an ultra-oligotrophic lake in East Antarctica, has the lake floor covered in benthic microbial mat communities, where laminated organo-sedimentary structures form with three distinct, sympatric morphologies: small, elongated cuspate pinnacles, large complex cones and flat mats. We examined the diversity of prokaryotes and eukaryotes in pinnacles, cones and flat microbial mats using high-throughput sequencing of 16S and 18S rRNA genes and assessed how microbial composition may underpin the formation of these distinct macroscopic mat morphologies under the same environmental conditions. Our analysis identified distinct clustering of microbial communities according to mat morphology. The prokaryotic communities were dominated by Cyanobacteria, Proteobacteria, Verrucomicrobia, Planctomycetes, and Actinobacteria. While filamentous Tychonema cyanobacteria were common in all mat types, Leptolyngbya showed an increased relative abundance in the pinnacle structures only. Our study provides the first report of the eukaryotic community structure of Lake Untersee benthic mats, which was dominated by Ciliophora, Chlorophyta, Fungi, Cercozoa and Discicristata. The eukaryote richness was lower than for prokaryote assemblages and no distinct clustering was observed between mat morphologies. These findings suggest that cyanobacterial assemblages and potentially other bacteria and eukaryotes may influence structure morphogenesis, allowing distinct structures to form across a small spatial scale.